2023
DOI: 10.1021/acs.jpcb.3c03125
|View full text |Cite
|
Sign up to set email alerts
|

Raman Imaging Reveals Insights into Membrane Phase Biophysics in Cells

Abstract: Cellular membranes are essential components of all living organisms. They are composed of a complex mixture of lipids with diverse chemical structures and crucial biological functions. The dynamic and heterogeneous nature of cellular membranes presents a challenge for studying their biophysical properties and organization in vivo. Raman imaging, particularly coherent Raman scattering techniques such as stimulated Raman scattering (SRS) microscopy, have emerged as powerful tools for studying cellular membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…243,244 In this regard, various alkyne-based Raman reporters have been developed for biological imaging via stimulated Raman scattering (SRS) microscopy. 245 In addition, Cho and co-workers 246,247 showed that addition of a heavy atom, such as silicon (Si) or selenium (Se), between the probe alkyne group and the parent molecule can significantly enhance the transition dipole moment and the vibrational lifetime of the corresponding C�C stretching vibration. While such strongly absorbing alkynes with long vibrational lifetimes are useful IR probes for nonlinear vibrational spectroscopy, they have not been widely used in biological studies.…”
Section: Alkyne Stretching Vibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…243,244 In this regard, various alkyne-based Raman reporters have been developed for biological imaging via stimulated Raman scattering (SRS) microscopy. 245 In addition, Cho and co-workers 246,247 showed that addition of a heavy atom, such as silicon (Si) or selenium (Se), between the probe alkyne group and the parent molecule can significantly enhance the transition dipole moment and the vibrational lifetime of the corresponding C�C stretching vibration. While such strongly absorbing alkynes with long vibrational lifetimes are useful IR probes for nonlinear vibrational spectroscopy, they have not been widely used in biological studies.…”
Section: Alkyne Stretching Vibrationmentioning
confidence: 99%
“…However, for an alkyne group attached to the side chain of an amino acid, the oscillator strength of its CC stretching vibration is typically very small, making it less useful in practice as an IR probe. However, it can be used as a site-specific Raman probe of protein structure and dynamics. , In this regard, various alkyne-based Raman reporters have been developed for biological imaging via stimulated Raman scattering (SRS) microscopy . In addition, Cho and co-workers , showed that addition of a heavy atom, such as silicon (Si) or selenium (Se), between the probe alkyne group and the parent molecule can significantly enhance the transition dipole moment and the vibrational lifetime of the corresponding CC stretching vibration.…”
Section: Vibrational Probesmentioning
confidence: 99%
“…For this reason, Raman spectroscopy has recently attracted growing attention in biochemical and biomedical research including cell biology and microbiology [27,[101][102][103][104][105]. The prospective areas of application in this field are sufficiently wide, see, e.g., the reviews cited above, but below, we restrict ourselves to those which are coordinated by their objects of investigation with other methods considered in our work.…”
Section: Some Modern Prospective Applications Of Raman Spectroscopymentioning
confidence: 99%
“…11–13 Raman imaging is a powerful method for studying intracellular lipids, membrane phase behaviour and lipid organisation. 14 For example, a recent report demonstrated quantitative chemical imaging of FAs based on chain length using C–C gauche modes in the region 1050–1140 cm −1 of the SRS spectrum. 15 With a spectral resolution <10 cm −1 , hyperspectral analysis was capable of discriminating mixtures of FAs in neat form using multivariate curve resolution, although the use of a femtosecond laser source for imaging is known to be cell damaging, which can limit some live cell applications.…”
Section: Introductionmentioning
confidence: 99%